Improvised Dialogue and Alliance of Religions in the Kenduri Tradition of Jatimulyo, Yogyakarta, Indonesia - Lathifatul Izzah; Chahya Kusuma; Lukman Hakim; Ahmad Salim; Fahmi Hidayati (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
This paper examines the role of the kenduri tradition as a medium for improvised interreligious dialogue and alliances in the multireligious community of Jatimulyo, Girimulyo Yogyakarta, Indonesia. Despite Indonesia's religious diversity and history of conflicts, kenduri persists as a way of life, fostering harmony amid differences in beliefs. The research problem centers on understanding why this community remains deeply rooted in kenduri and how it generates organic dialogue and cooperation across religions, addressing gaps in prior studies that overlook its improvisational aspects in building tolerance. Employing a qualitative ethnographic approach, data were collected through participatory observation, in-depth interviews, and documentation. Findings reveal that Kenduri’s a culture and tradition that has become a way of life and even the life style of the community. Based on its implementation, there are 3 types of kenduri, namely religious, traditional, and cultural. All three types of kenduri gave birth to a process of dialogue and alliance. Ultimately, kenduri serves as a powerful instrument for fostering interfaith harmony, presenting a compelling model for inclusive societies. It should therefore be deliberately integrated into multicultural policies and educational frameworks as a practical and culturally grounded approach to promoting social cohesion.